2015
DOI: 10.1080/10286020.2015.1096269
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds from the twigs and leaves of Tara (Caesalpinia spinosa)

Abstract: Two new homoisoflavans, 4'-hydroxy-7-methoxy-3-benzyl-2H-chromene (1) and 3,4-cis-di-O-3-hydroxy-7-methoxy-3-(4-hydroxybenzyl)-4-ethoxychroman (2), one new coumarin, 7-methoxy-3-(4-hydroxybenzyl)coumarin (4), together with seven known phenolic compounds, bonducellin (3), anemarcoumarin A (5), (+)-syringaresinol (6), curuilignan D (7), scopoletin (8), and p-hydroxybenzaldehyde (9), were isolated from Tara (Caesalpinia spinosa Kuntze). The structures of the new compounds were characterized from their 1D and 2D N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…The methods for these calculations are supported in the literature [23,24]. As a result of this study, we can assume that piperine may be interact with the blood compounds in the similar way.…”
Section: A= -Elumomentioning
confidence: 58%
See 1 more Smart Citation
“…The methods for these calculations are supported in the literature [23,24]. As a result of this study, we can assume that piperine may be interact with the blood compounds in the similar way.…”
Section: A= -Elumomentioning
confidence: 58%
“…Calculation of the polarity of the measurement of the dipole moment, considering the dipole moment vector of each bond is present in the form of the resultant moment vector [22]. He et al emphasized that the plant's active compound were isolated with ethanol efficiently [23]. Piperine can dissolves in blood and reaches every tissue of the body because of having a high dipole moment.…”
Section: A= -Elumomentioning
confidence: 99%
“…Detailed analysis of the 2D NMR spectra and the correlations listed in Table 1 allowed to elucidate the structure of compound 1 as 3-(2-hydroxy-4-methoxybenzyl)chromane-4,7-diol. In related homoisoflavonoids (sappanins), the benzyl ring usually is monosubstituted (in the para position at C-4′) or disubstituted (2 substituents in ortho-position at C-3′ and C-4′), associated with chemical shifts between δ C 140 and 150 Zhao et al 2014;He et al 2016;Abegaz and Knife 2019), but in compound 1, these shifts were not observed. A meta-substitution (at C-4′ and C-6′) is unusual.…”
Section: Resultsmentioning
confidence: 99%
“…En particular, la tara (Caesalpinia spinosa), un arbusto de tipo leguminosa originario del Perú que predomina en zonas secas y valles interandinos de Suramérica (He et al, 2016), se aprovecha en la industria química (taninos), alimenticia (aditivo hidrocoloide) y farmacéutica (ácido gálico, antioxidante) (Melo et al, 2013). Los taninos de C. spinosa son usados en medicina tradicional por sus propiedades antiinflamatorios, antimicóticos, antibacterianos, antisépticos, antitumorales y antioxidantes (Murga et al, 2016); su contenido de taninos está en un rango de 0,2 a 25% del total de masa seca, dependiendo de la especie vegetal, tiempo de cosecha, hábitat y método de extracción (Cuong et al, 2020).…”
Section: Introductionunclassified